AVTOMOBILLARDAN CHIQAYOTGAN GAZLAR VA ULARNING ATROF-MUHITGA TA’SIRI - R.Rapiqjonov, (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
This article examines the detrimental effects of automobile exhaust gases on the environment, human health, and plant life. These gases contain carbon monoxide, nitrogen oxides, sulfur dioxide, and other harmful substances that pollute the air and accelerate global warming. For humans, exposure to these pollutants can lead to respiratory diseases, cardiovascular issues, and allergic reactions. Toxic emissions slow down growth and reduce crop yields. Therefore, it is crucial to use eco-friendly technologies to minimize vehicle emissions.